Team perceived virtuality: Empirical exploration of its two dimensions - Costa, P.; Handke, L.; König, M.; Thieme, O. (Group Dynamics: Theory, Research, and Practice, 2024)
Objective: The present study aims at empirically exploring the construct of team perceived virtuality (TPV), validating its proposed bidimensional structure and predictive validity for affective and performance outcomes. Method: Three samples of 95 mix-gender, educated and Western teams, answered an online survey on team perceived virtuality (in form of collectively experienced distance and collectively experienced information deficits) teamwork engagement and team performance. Sample 1 consisted of 84 individuals, 63% female and 81% under 40 years of age. Sample 2 consisted of 68 individuals, 25% female and 64.2% under 40 years of age. Sample 3 consisted of 122 individuals, 53% female and 66% under 40 years of age. Results: The fit of a two-factor model (?² = 195.98, df = 20, p < .001, comparative fit index, CFI = 0.72, RMSEA = 0.18, SRMRwithin = 0.12) supported the bidimensional structure of the construct, and measurement invariance across samples was supported. Only distance is a significant predictor of teamwork engagement (? = −.50, p = .007); only information deficits (? = −.36, p = .076) are a significant marginal predictor of team performance; and both distance (? = −.33, p = .029) and information deficits (? = −.48, p = .002) are predictors of team adaptive performance, with the latter having a greater predictive power. Conclusions: This study provides evidence of team perceived virtuality as a team-level construct, validates its two-factor structure, and demonstrates the differential relationship between its two constituting dimensions and performance-related and affective-motivational outcomes, respectively. The generalizability of the findings is limited by samples’ characteristics.